Photodynamic therapy for epithelial malignant neoplasms of skin - V. N. Kapinus; M. A. Kaplan; I. S. Spichenkova; A. M. Shubina; E. V. Yaroslavtseva-Isaeva (Biomedical Photonics)
The results of photodynamic therapy (PDT) in patients with skin cancer are represented. The treatment was performed in 283 patients with basal cell skin cancer (BCSC) and also in 51 patients with squamous cell skin cancer (SCSC). For PDT the photosensitizer Photolon at dose of 1.1–1.6 mg/kg body weight was used. The light irradiation dose delivered to tumor was from 100 to 600 J/cm2 by one or several fields according to type and size of tumor lesion. After PDT for BCSC the complete regression of tumor lesions was in 96.8% of cases, partial regression – in 3.2%. For PDT of recurrent tumors the complete regression was observed in 76.4% of cases, partial regression – in 23.6%. After PDT in patients with primary SCSC the complete regression was achieved in 91.7% of patients and partial regression – in 8.3%. For treatment of recurrent SCCS the complete regression was observed only in 59.3% of cases, partial – in 33.3%, no response – in 7.4%. For follow-up period from 6 months to 5 years recurrent SCSC was diagnosed in 31.2% of patients. The results shows that the application of PDT allows to perform effective treatment of basal and squamous cell skin cancer for unfavorable localization of tumor and in case of limitations for surgical treatment and/or radiotherapy and the efficacy of treatment depends on stage of disease. clinical and morphological pattern of process and previous treatment modality.